STUDI PELAKSANAAN KEBIJAKAN PERATURAN DAERAH JAMINAN KESEHATAN DAERAH SUMATERA BARAT SAKATO DALAM MENGHADAPI UNDANG-UNDANG SISTEM JAMINAN SOSIAL NASIONAL DAN UNDANGUNDANG BADAN PENYELENGGARA JAMINAN SOSIAL TAHUN 2013 - Tuty Ernawati (Jurnal Kebijakan Kesehatan Indonesia, 2013)
ABSTRACTBackground: Local health insurance (Jamkesda) is an effortmade by the Government of West Sumatra province to improvethe accessibility of health services for the poor or near poorwho are not accommodated in the quota of public healthinsurance (Jamkesmas). Jamkesda was implemented at thestart of 2007 until in 2011 using Governor Regulation WestSumatera Number 40 and Number 41 in 2007. After runningfor five years, there are still many problems in theimplementation. Later in 2011, the provincial parliament of WestSumatera exercised its rights of initiative and enacted LocalLegislation Number 10 year 2011 regarding the implementationof the Health Insurance West Sumatra Sakato. Afterwards,the implementation of Jamkesda West Sumatera Sakato refersto these regulations. The purpose of this study is to evaluatethe implementation of the new regulation of the Jamkesda WestSumatera Sakato in 2013.Methods : This study is a descriptive analysis with a qualitativeusing case study. Data collection is done at the ProvincialHealth Office / District Health Office / City selected, PT HealthInsurance, regional planning agency (Bappeda), and healthprovider. Qualitative data were collected through in-depthinterviews, and secondary data were collected throughdocument review.Result: The results of the study shows that implementation ofhealth insurance on West Sumatra Sakato still had not beenoptimal, namely how the selection of the participants; a lowpremium that is Rp.6.000/month/member by sharing fundingbetween provincial and district budgets / City budgets; thebenefits are not yet comprehensive enough; health providersis still limited in the region of West Sumatra province and onlyin public facilities; health workers has not been evenlydistributed; the team is still not functioning well; the monitoringand evaluation at every level Administrative as well associalization of Jamkesda are not optimal; and the existingpolicy has not referred to higher level policy.Conclusion: Implementation of Jamkesda West SumatraSakato does not go according to the existing policy. Amongothers, the selection of membership, quality of health care,lowpremiums, health facilities are limited, health workers have notbeen evenly distributed, and the monitoring and evaluationteam has not been established as per the guidelines.Suggestion: There is a need to evaluate Jamkesda WestSumatera Sakato policy so that the policies are notcontradicting. There is a need to form a Monev Team forJamkesda so that all parties have a sense of sharedresponsibility.Keywords: Local Regulation of Jamkesda, health financing,Provider Jamkesda.